Ceramide signaling in immunity: a molecular perspective - Himani Thakkar; Vinnyfred Vincent; Bhagirath Chaurasia (Lipids in Health and Disease)
Abstract Ceramides are bioactive lipids that play a crucial role in cellular signaling and structural integrity (Nat Rev Mol Cell Biol 19:175-191, 2018). As members of the sphingolipid family, ceramides consist of a sphingoid base attached to a fatty acid (Annu Rev Biophys 47:633-654, 2018). Their unique structure confers both hydrophobic and amphipathic properties, enabling them to organize into membrane microdomains that influence cellular dynamics (Annu Rev Biophys 47:633-654, 2018). In recent years, ceramides have garnered attention for their role in modulating a range of cellular and organismal functions. Unlike other lipids that primarily serve structural roles, ceramides act as bioactive lipids in key signaling pathways, mediating stress responses such as inflammation, oxidative stress, growth inhibition, metabolism, autophagy, and apoptosis (J Lipid Res 60:913-918, 2019). Their regulatory effects are particularly important in immune cells, where ceramides can influence cell fate, modulate cellular metabolism, affect cytokine production, and dictate responses to external stimuli (Nature 510:58-67, 2014). Since ceramides maintain a dynamic equilibrium with other sphingolipids within a cell, understanding their role in immune cells in isolation provides only a partial perspective. Nevertheless, as a bioactive lipid and the central precursor of other sphingolipids, ceramides play a pivotal role in immune cells, deserving focused attention.